The value of 18F-FDG-PET/CT in identifying the cause of fever of unknown origin (FUO) and inflammation of unknown origin (IUO): data from a prospective study. Issue 1 (19th September 2017) - Schönau, Verena; Vogel, Kristin; Englbrecht, Matthias; Wacker, Jochen; Schmidt, Daniela; Manger, Bernhard; Kuwert, Torsten; Schett, Georg
Abstract : Background: Fever of unknown origin (FUO) and inflammation of unknown origin (IUO) are diagnostically challenging conditions. Diagnosis of underlying disease may be improved by 18 F-fluorodesoxyglucose positron emission tomography ( 18 F-FDG-PET). Methods: Prospective study to test diagnostic utility of 18 F-FDG-PET/CT in a large cohort of patients with FUO or IUO and to define parameters that increase the likelihood of diagnostic 18 F-FDG-PET/CT. Patients with FUO or IUO received 18 F-FDG-PET/CT scanning in addition to standard diagnostic work-up. 18 F-FDG-PET/CT results were classified as helpful or non-helpful in establishing final diagnosis. Binary logistic regression was used to identify clinical parameters associated with a diagnostic 18 F-FDG-PET/CT. Results: 240 patients were enrolled, 72 with FUO, 142 with IUO and 26 had FUO or IUO previously (exFUO/IUO). Diagnosis was established in 190 patients (79.2%). The leading diagnoses were adult-onset Still's disease (15.3%) in the FUO group, large vessel vasculitis (21.1%) and polymyalgia rheumatica (18.3%) in the IUO group and IgG4 -related disease (15.4%) in the exFUO/IUO group. In 136 patients (56.7% of all patients and 71.6% of patients with a diagnosis), 18 F-FDG-PET/CT was positive and helpful in finding the diagnosis. Predictive markers for a diagnostic 18 F-FDG-PET/CT were age over 50 years (p=0.019), C-reactive protein (CRP) level over 30 mg/L (p=0.002) and absence of fever (p=0.001). Conclusion: 18 F-FDG-PET/CT scanning is helpful in ascertaining the correct diagnosis in more than 50% of the cases presenting with FUO and IUO. Absence of intermittent fever, higher age and elevated CRP level increase the likelihood for a diagnostic 18 F-FDG-PET/CT.